Molecular-level evaluation of thermal field confinement effects on moisture distribution at the interface of natural ester oil-paper insulation: An investigation of electric field correlation - Zhou, Jian; Huang, Zhengyong; Wang, Feipeng; Wang, Qiang; Zhang, Kai; Zuo, Haochen (Journal of molecular liquids, 2023)
•The diffusion of water molecules enhanced by increasing temperature, with anisotropic diffusion coefficients.•Viscous force hindrance trapped almost all water molecules at the oil-paper insulation interface.•Under the combined influence of temperature and electric field, the number of water clusters at the interface increased.•The water diffuses differs significantly when electric field is normal to the interface compared to tangential interface.•Water molecules polarized in the direction normal to the insulation interface require a higher electric field strength. Oil-paper insulation is commonly used in transformers and is subject to dynamic changes in moisture content and distribution due to the influence of multiple physical fields such as temperature and electric fields. Moisture at the interface of oil-paper insulation can distort the interfacial electric field and cause insulation failure, but it is difficult to measure and characterize. In this study, molecular dynamics was used to simulate the diffusion behavior of water molecules at the interface of natural ester oil-paper insulation at temperatures ranging from 298 to 373 K, and the effect of electric fields on water diffusion was also analyzed. The results showed that without an electric field, water molecules in natural ester insulating oil tend to cluster at 298 K. Water molecules gradually diffuse towards the interface of the natural ester oil-paper insulation, but most remain at the interface and are difficult to penetrate into the cellulose insulating paper. In addition, normal diffusion is gradually enhanced at 298–328 K, reaching a minimum at 343 K. The interaction energy between water molecules and natural ester insulating oil decreases with increasing temperature, while the interaction energy with cellulose insulating paper decreases and then increases, reaching a minimum at 343 K. The combined influence of temperature and electric fields leads to an increase in the number of water clusters at the oil-paper interface. The interaction energy between water molecules and both natural ester insulating oil and cellulose insulating paper is enhanced, inhibiting the diffusion of water into the insulating paper. It was also found that the ability of water to diffuse differs significantly when the electric field direction is normal to the interface compared to when it is tangential to the interface. This is due to the fact that the water molecules when subjected to electric field action turn to polarize, and their electric field direction diffusion coefficient decreases, but still much higher than the non-electric field action direction. Further, the study found that the natural ester oil-paper insulation interface polarization is directional, and water molecules polarized in the direction normal to the insulation interface require a higher electric field strength.